Polyelectrolyte Complex-based Multiparticulate Drug Delivery System: A Special Emphasis on Chitosan and Alginate (Asian Journal of Pharmaceutics (AJP), 2024)
Effective drug delivery systems play a pivotal role in optimizing therapeutic outcomes and minimizing sideeffects. This study explores the potential of a multiparticle drug delivery system incorporating chitosan, alginate,and polyelectrolyte as a versatile platform for controlled and targeted drug release. These materials offer distinctattributes that synergistically enhance drug bioavailability, stability, and release kinetics. With its bioadhesiveproperties and biocompatibility, chitosan promotes prolonged residence time in the gastrointestinal tract, therebyimproving drug absorption. Alginate contributes to the system’s stability and protection of encapsulated drugs,while also allowing modulation of release profiles. The inclusion of polyelectrolytes offers an additional layer ofcontrol over swelling behavior and encapsulation efficiency. The multiparticulate nature of the system addresseschallenges associated with dose uniformity and release consistency. This approach provides advantages in terms ofenhanced drug dispersion, reduced risk of dose dumping, and potential for tailored release patterns. Furthermore,the system’s adaptability enables the design of complex delivery strategies, including sequential or combinationtherapies. However, formulation optimization remains a critical factor in achieving desired release profilesand therapeutic effects. Challenges in maintaining batch consistency and scaling up production also warrantconsideration. As the field of pharmaceutical science continues to advance, this multiparticulate drug deliverysystem holds promise for revolutionizing drug administration, resulting in safer and more effective treatmentsfor various medical conditions. Further research and development in this area are warranted to fully harness itspotential.